In vivo human skin penetration of (–)-epigallocatechin-3-gallate from topical formulations - Scalia Santo; Trotta Valentina; Bianchi Anna (Acta Pharmaceutica)
The aim of the study was to examine the effect of topical vehicles on the in vivo human stratum corneum penetration of the antioxidant and skin photoprotective agent (-)-epigallocatechin-3-gallate (EGCG). Model oil-in-water (o/w) emulsion and gel formulations containing 1 % (m/m) EGCG were prepared and subjected to photodegradation studies in order to select excipients that minimize the light instability of EGCG. The optimized emulsion and gel were applied to human volunteers and the EGCG percutaneous permeation was evaluated in vivo by the tape- -stripping technique. No significant differences in the percentage of the applied EGCG dose diffused into the stratum corneum were observed between the o/w emulsion (36.1 ± 7.5 %) and gel (35.5 ± 8.1 %) preparations. However, the amount of EGCG permeated into the deeper region of human stratum corneum was significantly larger for the o/w emulsion compared to the gel. Therefore, the emulsion represents a suitable vehicle for topical delivery of EGCG.